GAYA BAHASA KIASAN DALAM DONGENG ANAK BERBAHASA INGGRIS (STUDI KASUS KARYA BROTHERS GRIMM) - Rosita Sofyaningrum (Ruang Kata, 2021)
The purpose of this study is to investigate the use of figurative language in English children's fairy tales by Brothers Grimm with titled Hansel and Gretel, Rapunzel, and Snowdrop. This study specifically addresses the style of figurative language contained in English children's fairy tales. Style of figurative language are examined in this study includes metaphor, personification, simile, and hyperbole, in terms of form, meaning, function, and particularities in English children's fairy tales. Advanced Research is a qualitative research produces descriptive data in the form of the written word. This study did not use statistical data in the form of numbers, but rather to describe the form, meaning, types, functions, and uniqueness of figurative language in English children's fairy tales. The results showed that in the style of figurative language metaphor based on Haley’s hierarchy in nine metaphors, the metaphors in the three fairy tales are being, cosmos, energy, terrestrial, object, animate, and human. Personification in this research are inanimate personification and non-human personification. Simile in this research includes abstract (being), objects, cosmos, terrestrial, plants, and animals. Hyperbole in this research is hyperbole that state a thing and hyperbole that state a situation. Function of figurative language in the fourth type of style are; reveal the beauty in the style of figurative language, declare an abstract in a concrete way to give a clear image, stating things that are not captured by human senses, and cause freshness or emphasis the words, to give emphasis to a statement or situation, to intensify and enhance the impression and impact of the intent to deliberately overstate the thing and circumstances. Uniqueness found in the using of vehicle from the figurative language in the form of terrestrial, cosmos, and animal. Through this study it can be concluded that children in Europe, the reader or the audience of this tale, is expected to know the figurative language style.